Various Moral Values in The Film ‘Cinta Subuh’ - Kusuma, Venina Dwita; Sunaiyah, Salma; Candra, Monica Septya Kartika; Agustina, Merlinda Putri; Yulaikha, Siti (Proceeding International Conference on Education, 2023)
This study aims to describe the moral values ​​in the film Cinta Subuh by Ali Farighi. As for specifically covering (1) What are the moral values ​​towards God used by the author in the film Cinta Subuh (2) What are the moral values ​​towards humans used by the author in the film Cinta Subuh and (3) What are the moral values ​​towards oneself used by the author in the film Cinta Subuh. This type of research is library research. The primary data taken from this study is the film Cinta Subuh. While secondary data, researchers took from various sources, ranging from books, journals, articles. The data collection technique in this research is a documentary study by collecting documents and data needed in the research. Data analysis used by researchers in this study, researchers used content analysis methods. Where content analysis is a technique used to draw conclusions. The results of the study show that the film Cinta Subuh contains several moral values. The moral values ​​contained therein contain many positive moral values. This can be indicated by the results of this study that: (1) there are several forms of moral values ​​towards God which the author includes in the characters in the film Cinta Subuh including prayer and tawakal. (2) there are also moral values ​​for fellow human beings in the film's actors, namely helping and compassion as well. (3) moral values ​​towards oneself in the form of moral courage and never giving up.